Lactobacillus casei Strain Shirota Enhances the Ability of Geniposide to Activate SIRT1 and Decrease Inflammation and Oxidative Stress in Septic Mice - Mai, Chao; Qiu, Li; Zeng, Yong; Tan, Xingqin (Frontiers in Physiology, 2021)
Gardenia jasminoides Ellis is rich in geniposide, which can be transformed into genipin for better efficacy, but genipin is unstable and difficult to preserve. The present study explored the effects and mechanism of Lactobacillus casei Strain Shirota (LcS) in enhancing the geniposide ability for sirtuin type 1 (SIRT1) activation to improve cognitive dysfunction in septic mice. Animal ethology and molecular biology methods were used to detect sepsis mice. Results showed that, when compared with the model group, LcS+geniposide could improve the mice survival rate; simultaneously, LcS+geniposide could also increase the total travel distance, the number of standing times, the amount of hair grooming, the duration in the target quadrant, and the number of crossing areas. Nerve cell testing showed that LcS+geniposide could reduce the nerve cell apoptosis rate caused by sepsis. LcS+geniposide could reduce the TNF-α, IL-6, IL-1β, and MDA levels in the hippocampus of septic mice and increase the enzyme activity (SOD, CAT). LcS+geniposide could also up-regulate the mRNA expression of SOD1, SOD2, and CAT in the hippocampus of septic mice and down-regulate the mRNA expression of TNF-α, IL-1β, NF-κB and p53. Simultaneously, LcS+geniposide could also up-regulate the SIRT1 protein expression and down-regulate the protein expression of Ac-FOXO1, Ac-NF-κB, and Ac-p53 in the hippocampus of septic mice. Animal experiment results showed that LcS+geniposide could improve the cognitive dysfunction of septic mice. Their effect was similar to that of the drug dexamethasone and stronger than geniposide alone. LcS could also enhance the geniposide ability for SIRT1 activation to improve the cognitive dysfunction of septic mice, and it could achieve the effect of the drug dexamethas.